Winner of the 2006/2007 RIWA Award (Evidence Based Library and Information Practice, 2007)
It is with great pleasure that the Research in the Workplace Award (RIWA)* assessment panel announces the winning proposal in 2006/2007 to be for a multi-site randomised controlled trial to determine the impact of providing a virtual reference service (Access Specialist Knowledge - ASK) to the local Primary Care and Mental Health Trusts within the UK National Health Service.